Alongwind load effects on free-standing lattice towers. Issue 155 (August 2016) - Calotescu, Ileana; Solari, Giovanni
Abstract: Free-standing lattice towers are structures used for various purposes such as radio and television broadcasting, electric power and microwave transmission, meteorological measurements, wind energy production and so on. Due to their properties, they are mainly sensitive to wind loads. A longstanding discussion on the wind loading effects on this structural type has been carried out in the literature. This paper investigates the alongwind load effects on free-standing lattice towers by introducing specific influence functions of displacements, shear forces, bending moments and axial forces in leg elements. Such influence functions are first derived, calibrated and validated for the most typical structural types, then they are used within the framework of the gust effect factor technique. Comparative studies with reference to both the traditional use of cantilever beam approaches and finite element methods point out the role of the bracing pattern and, more precisely, of the level of the crossing of diagonals in tower panels. All the applications developed here refer to real structures with different properties. Results are interpreted and compared with those provided by previous studies on this structural type. Engineering and design issues are discussed focusing on the most critical aspects concerning dynamic wind loads. Highlights: Alongwind load effects on freestanding lattice towers are investigated. Specific influence functions of wind load effects are introduced. Comparisons among FEM, classical e new influence function methods are carried out. The key element of structural behavior is the bracing pattern of tower panels.